East Binjai Shopping Center and Recreation - Firman Eddy; T. Hasyiral Haikal (International Journal of Architecture and Urbanism, 2018)
Binjai is one of the cities included in the Mebidangro development project which includes Medan City, Binjai City, Deli Serdang Regency, and Karo Regency. Strategic location located on the road cross Sumatera make Binjai City a prosperous city in its development. The economic condition of the city of Binjai in the previous few years continues to increase, in the sector of Large and Retail Trade. Based on survey results, the city of Binjai still needs a center of excellence and recreational facilities such as cinemas and eating places to improve the economic quality of the city. The adhesive of East Binjai Shopping and Recreation Center is expected to meet those needs. The hot temperature of the city of Binjai becomes the designer's choice of theme "Green Architecture" as the design theme. It is considered very suitable for heat temperature to the building. A design approach that carries the theme of Green Architecture can create environmentally friendly buildings. Implementation of this theme is also useful to save the operational costs of the building.